Biologics for Psoriasis During the COVID-19 Pandemic - Zeng, Huanhuan; Wang, Siyu; Chen, Ling; Shen, Zhu (Frontiers in Medicine, 2021)
Coronavirus disease (COVID-19), a new form of acute infectious respiratory syndrome first reported in 2019, has rapidly spread worldwide and has been recognized as a pandemic by the World Health Organization. It raised widespread concern about treatment of psoriasis in this COVID-19 pandemic era, especially on the biologics uses for psoriatic patients. This review will summarize key information that is currently known about the relationship between psoriasis, biological treatment and COVID-19, as well as vaccination related issues. Then provide reference for dermatologists and patients when they need to make clinical decisions. Currently, there is no consensus on whether biological agents increase the risk of coronavirus infection, however current research shows that biological agents have no adverse effects on the prognosis of COVID-19 patients with psoriasis. In short, it’s not recommended to stop biological treatment to prevent the infection risk, and for those patients who tested positive for COVID-19, the decision to pause biologic therapy should be considered on a case- by- case basis and should take into account individual risk and benefit. Vaccine immunization against SARS-CoV-2 infection is strictly recommendable in psoriatic patient without discontinuation of their immunomodulatory therapy, but evaluating the risk-benefit ratio of maintaining the ongoing immunosuppressive therapy before performing the vaccine is mandatory at the moment.